Spin-orbit interactions between interchain excitations in conjugated polymers - Barford, W; Bursill, R; Makhov, D (2010)
Motivated by the reported enhanced singlet exciton yield in light-emitting polymers, we investigate spin-orbit coupling between Coulombically bound interchain excitations. We show theoretically that because of the close similarity of the singlet and triplet interchain wave functions, spin-orbit coupling between these states is negligible. Using density matrix renormalization group calculations on model systems, we confirm these theoretical predictions: spin-orbit coupling between interchain states is typically 103 - 104 times smaller than between corresponding intramolecular states, being typically ca. 1× 10 -7 eV for disordered polymers. We discuss the implication of these results for the possibly enhanced singlet exciton yield in light-emitting polymers. © 2010 The American Physical Society.